Mexican System Nationalization Supporter (Andamios, Revista de Investigación Social, 2013)
The paper aims to present levels of nationalization that has acquired the Mexican party system since the presidential election of 1994 to the latest 2012. To this end, use indexes of variation and  dispersion in order to analyze the vote of the main political forces. It is argued that the different geographical constituencies have become increasingly homogeneous in terms of electoral political behavior, as there is a tendency of political parties, particularly the opposition to the PRI, to improve performance in the different regions of the country.
Keywords: Nationalization; Cleavages; Party Systems; Political Behavior; Presidential Elections